Electric double layer overlap limits flow rate in Janus electrocatalytic self-pumping membranes. (10th September 2022) - Fang, Yuhang; Wereley, Steven T.; Moran, Jeffrey L.; Warsinger, David M.
Highlight: Self-pumping flow is an electroosmotic flow driven by self-generated electric field. The self-generated electric field arises from reaction-induced charge polarization. Self-pumping fluid speed can be increased 20-fold by avoiding EDL overlap. As EDLs separate, electromigration more strongly influences ion transport. Abstract: Nanoporous membranes with platinum (Pt) and gold (Au) coated on opposite faces can autonomously pump fluid in the presence of hydrogen peroxide, but the physics is not fully understood. Here, we show with simulation results that the self-pumping flow rate can be considerably increased by avoiding the overlap of electric double layers (EDL) inside pores. Due to catalytic electrochemical reactions on Pt and Au, hydrogen ions (H + ) are generated and depleted on opposite sides of the membrane, establishing a self-generated electric field and associated electro-osmotic flow through the pores. By optimizing the pore radius, EDL overlap is avoided and an area-averaged self-pumping flow speed of 23 µm/s can be achieved, which is 20 times higher than previously reported. By conducting the first-ever physico-chemical computational model of self-pumping membranes, this work reveals the mechanism of self-pumping flow in porous two-sided "Janus" membranes and highlights the potential of developing biomimetic membranes and lab-on-chip devices that can precisely and remotely control fluid flow in pores or channels in an "on/off" manner. Graphical abstract: Image, graphical abstract